2019
DOI: 10.1049/iet-cvi.2019.0085
|View full text |Cite
|
Sign up to set email alerts
|

Crowd counting using a self‐attention multi‐scale cascaded network

Abstract: Recent developments of crowd analysis and behaviour prediction have attracted much attention. Crowd counting, as the essential and challenging task in crowd analysis, is riddled with many issues, such as large scale variations, serious occlusion, and so on. In this study, a self-attention-based multi-scale cascaded network called SAMC-Net to estimate density map for crowd counting, especially for high congested scene, is proposed. The proposed SAMC-Net consists of two components: a classification sub-network f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…We compare the proposed Count‐DANet with several crowd counting methods, and the detailed results are shown in Table 2. It can be observed from Table 2, Count‐DANet has an 8.7% improvement of MAE with Li et al [16] on the Mall dataset. The estimated density maps by Count‐DANet and the ground truth of several samples on Mall datasets are shown in Fig.…”
Section: Methodsmentioning
confidence: 68%
See 2 more Smart Citations
“…We compare the proposed Count‐DANet with several crowd counting methods, and the detailed results are shown in Table 2. It can be observed from Table 2, Count‐DANet has an 8.7% improvement of MAE with Li et al [16] on the Mall dataset. The estimated density maps by Count‐DANet and the ground truth of several samples on Mall datasets are shown in Fig.…”
Section: Methodsmentioning
confidence: 68%
“…Shanghaitech_A contains 482 images, where 300 images are used for training, and the remaining images are for testing. We compare our method with several typical crowd counting methods on Shanghaitech_A dataset: Marsden et al [29], Zhang et al [12], Sindagi and Patel [18], Sam et al [13], Li et al [16], SaCNN [14], Li et al [19], and Zhang et al [15], the results of which are shown in Table 3. As is shown in Table 3, the proposed method gets a 0.3% improvement of MAE with Li et al [19] and achieves the lowest 85.9 of MAE among them, except the method proposed in [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mall dataset is similar to UCSD, which contains single scene and a small number of pedestrians. On this dataset, this work gets the best result compared with [7, 8, 42, 43, 44]. It shows that MSR‐FAN has good generalization ability for general datasets.…”
Section: Methodsmentioning
confidence: 85%
“…Even compared with the recently proposed MGANet [57], the MAE and MSE indicators of SCFFNet also decreased by 31.8% and 27.1%. is means that in extremely congested crowd scenes, the multiscale context feature fusion module is applied to model multiscale contextual features, an attention mechanism is introduced to process the extracted features, and attention [49] 467.0 498.5 MCNN [12] 377.6 509.1 FCN [53] 338.6 424.5 Switch-CNN [47] 318.1 439.2 CP-CNN [23] 295.8 320.9 DR-ResNet [52] 307.4 421.6 CSRNet [5] 266.1 397.5 SANet [22] 258.4 334.9 SAMC-net [54] 250.8 375.1 SCAR [43] 259.0 374.0 Multiscale-CNN [28] 264.9 382.1 LGCCNN [55] 336.5 510.2 SCLNet [24] 258.9 326.2 Khan and Basalamah [58] 229.4 325.6 ED-CNN [56] 271. information is obtained from the channel and spatial dimensions, which effectively solves the problems of complex background, scale variation, and occlusion in congested scenes. Figure 10 shows the visualization of some samples of the UCF_CC_50 dataset, from which we can see that SCFFNet performs well in crowd scenarios with different levels of congestion.…”
Section: Ucf_cc_50mentioning
confidence: 99%